Jenis Upaya Pada Peningkatan Kompetensi Tenaga Didik Pada Smp Negeri 4 Medan Melalui Pelatihan Tindakan Kelas - Arlina Arlina; Mutia Salwa Humairoh; Fitri Amelia; Nur Fauziyah; Anisa Putri (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
This research is aimed at increasing the competence of students at SMP Negeri 4 Medan in North Sumatra. There is an increase in the competence of trained personnel carried out by conducting Classroom Action Research (CAR). In Classroom Action Research Training (PTK) it is carried out by means of the cycle method which is carried out with various stages such as helping with problems, planning, action, observation, and reflection. From the research, it was found that there were problems where students were often confused and had difficulties at the stage of preparing and forming PTK when doing it in class. Due to their weak ability at the stage of establishing PTK due to limitations regarding understanding of CAR in practice and materially. Data collection techniques implemented in this study were used by means of observation, interviews and evaluation. In this study, it was found that the students played an active role in activities and they had seriousness, willingness, and high motivation in PTK. So that in PTK this increases the competence of teachers and is more courageous in creating a work on PTK activities. [10:42:52 PM]